Kidneys cytomembranes stability in pregnant women with type 1 diabetes and pregnancy outcomes depending on the method of insulin delivery - Zulfiya Raisovna Alimetova; Farida Vadutovna Valeeva (Сахарный диабет)
Objective. To evaluate of kidney cytomembranes stability during pregnancy and its outcomes in patients with diabetes mellitus type on type 1 with different stages of diabetic nephropathy (DN) according to the route of insulin administration. Materials and Methods. We study 100 pregnant women with type 1 diabetes with the introduction of insulin in the mode of multiple subcutaneous injections (MSII) and with portable dispenser with a continuous subcutaneous insulin infusion (CSII). DN stage determined by the level of albumin in the daily urine. Cytomembranes stability assessment conducted on daily excretion of ethanolamine and phospholipids with urine in each trimester. Pregnancy outcomes were analyzed in 52 patients with type 1 diabetes. In the group of pregnant women with delivery at term 38-40 weeks we also analyzed the status of newborns. Results. Indicators of cytomembranes stability of kidneys in pregnant women on CSII consistent with those in healthy pregnant women (p>0.05) the whole pregnancy, regardless of the level of daily urinary albumin excretion. There were no differences in cytomembrana stability of kidneys between the group of patients on MSII with normal albumin excretion (NAU) and the control group regardless to the gestational age (p>0.05). With the introduction of insulin in the mode of MSII on the stage of microalbuminuria (MAU) in the 3rd trimester we found the increase of ethanolamine excretion as compared to control groupy (U=8,00, p=0.012) and the group on CSII with a similar stage of nephropathy (U=2.00, p=0.033). In patients with proteinuria (PU) in the group on the MSII in the third trimester phospholipids excretion is increased with a daily urine (U=27,5, p=0.03 and U=22,00, p=0.07 for patients MSII and CSII, respectively). The use of an insulin pump allowed to prolong gestational period, even in severe proteinuric stage of nephropathy. Manifestations of diabetic fetopathy as macrosomia, hypoglycemia in the fetus at birth time mothers using CSII mode were less common than with MSII (p=0.01 and p=0.04, respectively). In the CSII group no resuscitation was needed, as opposed to 20% of children whose mothers used the MSII. Conclusion. The administration of insulin using portable dispenser the of mode CSII during pregnancy in patients with type 1 diabetes, even at the initial stage of the DN the cytomembranes stability is saved, pregnancy outcomes are improved.